2006
DOI: 10.1093/pubmed/fdl066
|View full text |Cite
|
Sign up to set email alerts
|

Informed choice in screening programmes: Do leaflets help? A critical literature review

Abstract: Research into informed choice in screening is hampered by the lack of agreement about its definition and measurement. The most effective way for screening programmes to achieve informed choice is unclear. Programmes should not rely solely on providing written information but should explore additional ways to promote informed choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 18 publications
1
50
1
1
Order By: Relevance
“…[5][6][7][8][9] A wider range of potential benefits for families have been proposed, including guidance for family planning, earlier diagnosis and avoidance of the 'diagnostic odyssey'. [8][9][10] NBS programs differ considerably with respect to parental educational materials 6,[11][12][13] and approaches to parental consent for screening. [6][7][8]14,15 In Canada, screening is considered routine and proceeds unless parents explicitly object -an opt-out approach.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] A wider range of potential benefits for families have been proposed, including guidance for family planning, earlier diagnosis and avoidance of the 'diagnostic odyssey'. [8][9][10] NBS programs differ considerably with respect to parental educational materials 6,[11][12][13] and approaches to parental consent for screening. [6][7][8]14,15 In Canada, screening is considered routine and proceeds unless parents explicitly object -an opt-out approach.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that providing balanced information to support informed decision making does not adversely affect participation in diabetes, breast cancer, or colorectal cancer screening (Fox R, 2006 to be screened (Adab P et al, 2003). They found that after adjusting for variables such as previous Pap test use, socio-economic status, and other preventive health behaviours, women exposed to the intervention brochure expressed a reduced willingness to be screened although the results of the study were not statistically significant.…”
Section: What Goals Values and Beliefs Should Be Considered When Mamentioning
confidence: 88%
“…18 A limitation of this study is that there is no general agreement on the definition of being adequately informed. 19 For this study, we focused on the level of knowledge and measured this by being able to answer four knowledgerelated statements correctly. We cannot exclude that participants were able to verify the answers in the information leaflet or guessed the right answer.…”
Section: Discussionmentioning
confidence: 99%